A Comparison of International and Domestic Hotels in Sanya, Hainan Province, China - Yi Du, Chuanchen Bi & Warangkana Thawornwiriyatrakul (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This paper focused on the hotel industry in Sanya, the southern city in HainanProvince, China. Its objective was to compare domestic 5-star with international 5-starhotel and to find out the differences between the two hotels. Using qualitative approachwith in-depth interview, observation and a systematic of review literature, we foundthe differences of each hotel operation and effective suggestions to make a betterdevelopment, according to their market environment. To understand these differences,the paper indicates them in the context of advantages, disadvantages and suggestions inthe competitive market environment.